Dermoscopy of skin infestations and infections (entomodermoscopy) - Part I: dermatozoonoses and bacterial infections, - Renato Marchiori Bakos; Clarissa Reinehr; Gabriela Fortes Escobar; Leandro Linhares Leite (Sociedade Brasileira de Dermatologia, 2022)
Abstract Dermoscopy is an essential in vivo diagnostic technique in the clinical evaluation of skin tumors. Currently, the same can also be said about its implications when approaching different clinical situations in Dermatology. A growing number of reports on dermatological scenarios and diseases have been published, in which dermoscopy has been of great diagnostic help. The term ‟entomodermoscopy" was coined to describe dermoscopic findings in skin infestations and also in dermatoses of infectious etiology. In part I of this article, the main dermoscopic descriptions of zoodermatoses and bacterial infections will be addressed. In many of them, such as scabies, pediculosis, myiasis, and tungiasis, it is possible to identify the pathogen and, consequently, attain the diagnosis more quickly and use the technique to follow-up therapeutic effectiveness. In other situations that will be described, dermoscopy can allow the observation of clinical findings with greater detail, rule out differential diagnoses, and increase the level of confidence in a clinical suspicion.